Harmonisasi Perjanjian Investasi Bilateral dengan Undang-Undang Penanaman Modal Pasca Sengketa Indian Metals Ferro Alloys LTD V. Indonesia: Menegaskan Entry Requirements Investor Asing - Endiva Yustiavandana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The 2015 dispute between Indian Metals Ferro Alloys Ltd v. Republic of Indonesia (PCA Case No.2015-40) marked an important moment in reaffirming the urgency of harmonizing domestic law with Bilateral Investment Treaties (BITs). It also emphasized the significance of entry requirements as the â€œgatewayâ€ of legality for foreign investors seeking to invest in Indonesia. Through this decision, the tribunal rejected IMFAâ€™s claim on the grounds that the company had failed to meet the principles of lawful establishment and due diligence, thereby demonstrating that compliance with Article 5(2) of the Investment Law is a crucial prerequisite for obtaining BIT protection. This research aims to explain how the lack of harmony between the Indonesia-India BIT and the Investment Law (UUPM) can give rise to investment disputes, and how the strengthening of legality/admission clauses, lawful establishment, and denial of benefits provisions within investment treaties is essential to maintain a balance between investor protection and the host Stateâ€™s regulatory sovereignty, while ensuring equitable legal protection for both parties.